LMD-05. Phase 1B Study of Avelumab and Whole Brain Radiotherapy (WBRT) in Patients with Leptomeningeal Disease (LMD): Preliminary Results. (9th August 2021) - Pina, Yolanda; Chen, Ann; Arrington, John; Macaulay, Robert; Tran, Nam; Liu, James; Mokhtari, Sepideh; Li, Jiannong; Law, Vincent; Sahebjam, Solmaz; Ahmed, Kamran; Creelan, Ben; et al.
Abstract: Background: LMD has a dismal prognosis with median survivals of 8–10 weeks. Recently the first phase 2 trial of PD-1 inhibitor monotherapy in solid tumor LMD showed median overall survival (OS) 3.6 months. We aimed to determine the safety/efficacy of avelumab with WBRT in patients with LMD from solid malignancies (NCT0371768). This combination can treat tumor directly and increase the permeability of the blood-brain-barrier with increased egress of activated T cells into the meninges/CSF and facilitated Avelumab entry into the CSF. Hypothesis: Combination radioimmunotherapy will produce an activated immunocyte/cytokine profile in CSF. Methods: Patients received concurrent Avelumab 800mg IV q2weeks x≤5 cycles with WBRT 3000cGy, 10 fractions. Primary endpoints: Safety/DLTs and OS at 3 months. Secondary endpoints: CSF T-cell/cytokine profiles (scRNAseq/phosophoproteomics) and clinical outcomes, to be performed when all 15 patients are accrued to minimize batch effects. Results: Ten patients (5 breast, 4 lung & 1 undifferentiated sinonasal carcinoma) were enrolled (n=8 females, n=2 males, ages 32–79); n=1 patient did not complete WBRT. Patients who received anti-PD-1/PD-1L/PD-L2/CD137/CTLA-4 therapy within 6 months prior to enrollment were excluded. 30% had grade 3 AEs at least possibly related to treatment (n=3 diarrhea, lymphopenia, decreased WBC count). There were no grade 4–5 toxicities. Six patients (66.7%) were alive at 3 months. The estimated median follow up in 9 patients (regardless whether patients failed or not) is 10.49 months (range, 0.95–19.82 months, 95% CI) and the estimated median follow up survival was 19.8 months assessed using the reverse Kaplan-Meier method. Median PFS is 4.27 months (range, 0.30–16.73 months, 95% CI). Conclusions: In this pilot study, combination of Avelumab and WBRT is safe, and demonstrates encouraging activity in patients with solid tumor LMD. Multiple platform interrogation of CSF may determine mechanisms of LMD therapeutic effects and differentiate responders from non-responders.